Properties of High-Energy Solar Particle Events Associated with Solar Radio Emissions - Ameri D; Valtonen E; Pohjolainen S (SPRINGER, 2022)
We have analysed 58 high-energy proton events and 36 temporally related near-relativistic electron events from the years 1997 - 2015 for which the velocity dispersion analysis of the first-arriving particles gave the apparent path lengths between 1 and 3 AU. We investigated the dependence of the characteristics of the proton events on the associations of type II, III, and IV radio bursts. We also examined the properties of the soft X-ray flares and coronal mass ejections associated with these events. All proton events were associated with decametric type III radio bursts, while type IV emission was observed only in the meter wavelengths in some of the events (32/58). Almost all proton events (56/58) were associated with radio type II bursts: 11 with metric (m) type II only, 11 with decametric-hectometric (DH) only, and 34 with type II radio bursts at both wavelength ranges. By examining several characteristics of the proton events, we discovered that the proton events can be divided into two categories. The characteristics of events belonging to the same category were similar, while they significantly differed between events in different categories. The distinctive factors between the categories were the wavelength range of the associated type II radio emission and the temporal relation of the proton release with respect to the type II onset. In Category 1 are the events which were associated with only metric type II emission or both m and DH type II and the release time of protons was before the DH type II onset (18/56 events). Category 2 consists of the events which were associated with only DH type II emission or both m and DH type II and the protons were released at or after the DH type II onset (31/56 events). For seven of the 56 events we were not able to determine a definite category due to timing uncertainties. The events in Category 1 had significantly higher intensity rise rates, shorter rise times, lower release heights, and harder energy spectra than Category 2 events. Category 1 events also originated from magnetically well-connected regions and had only small time differences between the proton release times and the type III onsets. The soft X-ray flares for these events had significantly shorter rise times and durations than for Category 2 events. We found 36 electron events temporally related to the proton events, which fulfilled the same path length criterion as the proton events. We compared the release times of protons and electrons at the Sun, and discovered that in 19 of the 36 events protons were released almost simultaneously (within +/- 7 minutes) with the electrons, in 16 events protons were released later than the electrons, and in one event electrons were released after the protons. The simultaneous proton and electron events and the delayed proton events did not unambiguously fall in the two categories of proton events, although most of the events in which the protons were released after the electrons belonged to Category 2. We conclude that acceleration of protons in Category 1 events occurred low in the corona, either by CME-driven shocks or below the CMEs in solar flares or in CME initiation related processes. It seems plausible that protons in Category 2 events were accelerated by CME-driven shocks high in the solar corona. Large delays of protons with respect to type III onsets in the events where protons were released after the electrons suggest late acceleration or release of protons close to the Sun, but the exact mechanism causing the delay remained unclear.